Praktik Oper Penumpang Angkutan Bus Antar Kota - Rusliyadi, Muhammad Rifqy; Karim, Kairuddin; Syahril, Muh. Akbar Fhad (Jurnal Litigasi Amsir, 2023)
This study aims to determine the factors that cause city transport passenger shift activities within the province at Lumpue Parepare type A terminal and to find out the legal review of passenger shift activities at Lumpue Parepare type A terminal. This research uses normative and empirical research with a statutory approach and a case passenger; Transport; Terminal. study approach, the data collection techniques used are observation, interviews, and documentation. Types and sources of data using primary data, secondary data, tertiary data, and data analysis were examined qualitatively and descriptively. The study’s results show what factors cause the activity of passing city transport passengers within the province at the type A terminal of Lumpue Parepare. The first is the loss experienced by bus transportation when it carries a few passengers or beyond the maximum target sea it carries. The second is bus routes. The third is that the bus violates itself outside the terminal which the driver carries out, while inside the terminal it is a passenger movement, not a passenger transfer activity. Fourth, the condition of the bus is not roadworthy for travel, and a legal review of passenger transfer activities at the Lumpue Parepare type A terminal, namely agreement law, consumer protection law, and transportation law.